Facing the City: Towards Artistic Research in High School Art Education - Greisberger, Eva (UXUC - User Experience and Urban Creativity, 2023)
End of June, somewhere in a museum in Vienna: countless students push and shove their way through an art exhibition. Teachers in between, with a wandering controlling gaze trying not to let their students out of sight. Employees of the museum dressed in special t-shirts, guiding groups of students through the museums’ space, leading from one artwork to the next, lingering briefly, explaining, asking questions, explaining further while moving slowly on to the next densely filled room—stale air. In this final week of school, museums, and their educational programmes, such as guided tours and workshops, are traditionally fully booked, often for months ahead. It is the time of the year when students and teachers go on field trips and leave the physical boundaries of their school building behind, at least for a few days. It is the time of the year when going for a school field trip becomes the phenomenon of a collective act: students and teachers explore the city to learn and teach outside the classroom. Because a school year is planned rigidly and learning outside the classroom demands additional organisation and effort, the last week of school is often the only time they are doing so.